Car Oil Usage Period Checking Application for Car Workshop Based on Mobile and Website - Prasasti Dani Harry Kuncoro; Adam Sekti Aji (STMIK Budi Darma, 2023)
Oil is an important part of a vehicle, especially the engine. Cars really need to pay attention to maintenance, especially when using the oil used in the engine. Until now, many car oil maintenance has not paid much attention, resulting in damage to the components in the engine, and also still few pay attention to the kilometre indicator that has been travelled on the speedometer as a reference in changing engine oil in the car. This research was made to provide solutions to existing problems and with the hope that this application can help car users in carrying out engine maintenance on vehicles used in a more effective and efficient way. In addition to changing the oil regularly according to the manufacturer's guidelines, vehicle owners also need to understand the importance of checking the oil level regularly and ensuring there are no leaks. By understanding the importance of car oil maintenance, vehicle owners can ensure optimal performance and avoid unnecessary engine damage, which in turn can save repair costs and extend vehicle life. The application developed is a REST API implementation created using Android Studio tools with a MySQL database as a place to store oil data on vehicles.